216k views
3 votes
3(2x-1)=5x+3+7x I do t get this cause I’m stupid

User Bhuvan
by
5.1k points

2 Answers

2 votes

Answer:

x=-1

Explanation:

3(2X-1)=5x+3+7x Distribute the 3 into the parenthesis

6x-3=5x+3+7x Isolate the x on one side

-6x -6x

-3=5x+3+7x-6x

-3 -3

-6=5x+7x-6x Add all the x's

-6=6x Divide 6 to isolate x

(-6)/6=(6x)/6

-1=x

Now you can check if it's right by inputting -1 for x and seeing if the equations equal each other

3(2(-1)-1)=5(-1)+3+7(-1)

3(-3)=-5+3-7

-9=-9 They equal each other so x=-1 is correct

User Ljtomev
by
5.8k points
1 vote

Answer:

x=-1

Explanation:

first you multiply 3 by whats in the parenthesis (you would get 6x-3)

then on the other side you combine like terms (add 7x plus 5x=12x)

Then you would isolate X to one side by subtracting 6x from 12x

Then you would subtract 3 from the side with 12x

By now your equation would be -6=6x

so you would divide both side by negative six to get x=-1

User Vollie
by
4.8k points